The road to Middle-earth : How J.R.R. Tolken created a new mythology - Shippey, T. A. (Boston : Houghton Mifflin Co., 2003)
"The Road to Middle-earth, Tom Shippey's classic work, now revised and expanded in paperback explores J.R.R. Tolkien's creativity and the sources of his inspiration. Shippey shows in detail how Tolkien's professional background led him to write The Hobbit and create a timeless charm for millions of readers. He argues convincingly that the source of Tolkien's inspiration lay not just in his love of fable but in his love of language. While examining the foundations and literary structures of Tolkien's most popular work, The Lord of the Rings, in rich detail, Shippey also discusses the contribution of The Silmarillion and Unfinished Tales to Tolkien's great myth cycle, showing how the more "difficult" books can be fully appreciated. He goes on to examine the remarkable twelve-volume History of Middle-earth, written by Tolkien's son and literary heir Christopher Tolkien, which traces the creative and technical processes by which Middle-earth evolved."--Jacket.
Acknowledgements and abbreviations -- Preface to the revised and expanded edition -- Lit. and lang. -- Philological inquiries -- Bourgeois burglar -- Cartographic plot -- Interlacements and the ring -- When all our fathers worshipped stocks and stones -- Visions and revisions -- On the cold hill's side -- Course of actual composition -- Afterword -- Tolkien's sources : the true tradition -- Four asterisk poems.
Includes bibliographical references (pages 362-379) and index.
Keywords: Tolkien, J. R. R. -- 1892-1973 -- Criticism and interpretation; Tolkien, J. R. R. -- 1892-1973 -- Knowledge and learning; Fantasy literature, English -- History and criticism; Middle Earth (Imaginary place); Myth in literature